KONSTRUKSI PENDIDIKAN ISLAM PERDAMAIAN PADA MASA RASULULLAH SAW - Fauziah Rusmala Dewi; Mukhlisin; Mohammad Thoriq Aqil Fauzi (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2023)
Islamic peace education is an effort to create a peaceful, tolerant andrespectful society of differences. The concept of Islamic peace educationbased on the Qur'an and Hadith is to create good and peaceful relationsbetween fellow Muslims, as well as maintaining the unity and unity ofMuslims by obeying the teachings of Allah SWT and His Messenger.Islamic peace education emerged as a response to the development of Islamas a major religion, as well as an effort to strengthen security and socialstability in society, in response to historical context, developments in scienceand technology, the phenomena of globalization and pluralism,strengthening unity, solidarity and harmonious relations between Muslimsand non-Muslim communities. Benefits and objectives of Islamic peaceeducation: (1) Forming a peaceful person, (2) Building harmoniousrelationships, (3) Cultivating an attitude of empathy, (4) Maintaining unityand unity, (5) Improving the quality of life, (6) Maintaining stability andsecurity , (7) Increasing understanding of the relationship between Islam andpeace, (8) Helping to build harmonious inter-religious relations, (9)Fostering attitudes and behavior based on peace, (10) Reducing levels ofconflict and violence, (11) Encouraging community formation MoreInclusive. During the period of Rasulullah SAW in Mecca, the constructionof Islamic peace education was built through: (1) Building awareness of theOneness of Allah SWT., (2) Building the values of honesty andtrustworthiness, (3) Increasing social awareness and concern, (4)Strengthening noble morals. The Islamic peace period of the ProphetMuhammad in Medina is known as the Medina Agreement or Misaq Medina.Peace construction steps: (1) formation of congregations or social groupsbound by the principles of justice and solidarity, (2) formation of agreementsbound by all social groups in Medina, (3) conflict resolution throughdialogue and deliberation.